ANALISIS WORK LIFE BALANCE DAN GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP KINERJA PEGAWAI ASN DI LINGKUNGAN SATPOL PP BENGKULU SELATAN - Martizon, Ade; Nengsih, Mimi Kurnia (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
Performance is a very important part in achieving company goals. Employee performance is influenced by many factors, including work life balance and democratic leadership style. The aim of this research is to determine work life balance and democratic leadership style on the performance of ASN employees in the South Bengkulu Satpol PP environment. This research was carried out at the South Bengkulu Satpol PP office. The type of research used in this research is quantitative descriptive. The sample in this study was 73 people with the sampling technique in this study being total sampling. Data collection techniques are observation, questionnaires and documentation. The data analysis technique used in this research is quantitative descriptive.The results show that work life balance has a significant effect on the performance of ASN employees at the South Bengkulu Satpol PP with tcount > ttable (3,769 > 1,9944) and (sig a = 0.000 < 0.050). The democratic leadership style has a significant effect on the performance of ASN employees at the South Bengkulu Satpol PP with tcount > ttable (3,616 > 1,9944) and (sig a = 0.001 < 0.050). The results of the F test show that the calculated F value is 34,770 > 3,13 with a significance value of 0.000 < 0.005, which means that there is a simultaneous significant influence of the work life balance variable and democratic leadership style on the performance of ASN employees at the South Bengkulu Civil Service Police Unit. The R Square value is 0.106, this means that the rise and fall of the dependent variable, namely employee performance, is influenced by the independent variables, namely work life balance and democratic leadership style, by 49,8%. Meanwhile, the remaining 50,2% is influenced by other variables. Keywords: Work Life Balance, Democratic Leadership Style, Performance